Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada Unit Penyelenggara Bandar Udara Tunggul Wulung Cilacap - Niken Afiana; Rosiana Ulfa (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
ABSTRACT, The influence of the work environment on employee performance is closely related to the process of achieving company goals. Employees will work productively or not depending on motivation, job satisfaction, stress levels, physical conditions of work, social pressures, and changes that occur that affect employee performance. The changes that have occurred at Tunggul Wulung Cilacap Airport include a decrease in the number of commercial aircraft passengers since the COVID-19 pandemic. So that the maintenance of the facility does not run intensively and the work is still done manually. The purpose of this study was to determine how much influence the working environment has on employee performance at UPBU Tunggul Wulung Cilacap. This study used an associative quantitative method using data from the results of distributing questionnaires to 74 employees with a sample selection using a simple random sampling approach. Data analysis techniques used in this study were validity tests, reliability tests, normality tests, homogeneity testing, simple linear regression tests, and the coefficient of determination using IBM SPSS Statistics 26. Based on the results of the research that has been done, the results of testing the work environment hypothesis show a t-count value of 6,180, or positive, with a significant level of 0.000. So with a t-count > t-table (6.180 > 1.993) and a significant level of less than 0.05 (0.000 0.05), the hypothesis in this study accepts H and rejects Ho. Through the results of simple linear regression calculations, the value of Y = 35,843 + 0,346X is obtained. Level 0.000 0.05, so the conclusion is that there is an influence of the work environment on employee performance. Based on the results of the determination coefficient, the value of R (R Square) 0.347 is equal to 34.79%, which means that the influence of the working environment on employee performance is 34.7%.